AJWAIN SEEDS AS CAPPING AGENT FOR Bi2O3 NANOFLAKES: SYNTHESIS AND GROWTH INHIBITING EFFICIENCY OF BACTERIA - SETHURAMAN, BHARANI DHARAN; CHANDRASEKAR, LAKSHMI PRABHA; SUBRAMANI, MANIKANDAN; ANILKUMAR, ASWATHY KARANATH; GANESH, MUNUSWAMY-RAMANUJAM; MOHANDOS, SIVAKAMI (International Journal of Current Pharmaceutical Research, 2023)
Objective: This work is mainly focused to determine the antibacterial activity of the green synthesized Bi2O3 nanoparticles against the bacterial strains, Staphylococcus aureus and Escherichia coli using resazurin as indicator. Methods: Bismuth oxide nanoparticles were synthesized from the precursor bismuth nitrate [Bi (NO3)3.5H20] by using trachyspermum ammi (ajwain) seed extract. To carry out these works, the synthesized Bi2O3 NPs undergone characterizations and were confirmed by UV-Vis, FT-IR, XRD, SEM and EDAX, TGA-DTA and DLS. Biological activity was done using a well diffusion method. Results: Bi2O3 NP's has been tested against bacteria (S. aureus and E. coli) in wells and shows blue colour, indicating bacterial growth inhibition in a dose-dependent manner for different concentrations. Conclusion: The biological studies were done with one gram-positive and one gram-negative bacteria to show the inhibiting efficiency. The synthesized bismuth oxide nanoparticles showed good anti-bacterial activity (different concentrations) against S. aureus and E. coli.